Smart Power Transmission System Using FACTS Device - Qazi Waqar Ali; Azzam ul Asar (Institute of Advanced Engineering and Science, 2013)
Making of smart grids puts mounting pressure on the nation’s aging electric power transmission system. Just planting additional towers and stringing more line won’t practice the nation’s electric power transmission infrastructure to meet up the energy challenges ahead. Smart grids stand geared up to play a much larger role in the energy equation for reduction of transmission line losses. The FACTS controllers come out with the capability of enhancing transmission system control, reliability, and operation. This paper will discuss and express how Static Synchronous Compensator (STATCOM) has effectively been applied to power system for efficiently regulating system voltage and thus increase system load ability. This paper investigates the effects of (STATCOM) on voltage stability of a power system at different positions.The simulation analysis of this paper can be used as guideline for power industry. The study is thereby simulated using the MATLAB/SIMULINK software and simulation results show that STATCOM is effective in midpoint voltage regulation on transmission line. In this paper comparison is also performed between STATCOM and SVC under fault condition and it is proved that STATCOM have the capacity to provide more capacitive power for the period of a fault than SVC.